Political change and economic development among the Ibans of Sarawak, East Malaysia - Jawan, Jayum (1991)
The thesis described politics and economic development among the Ibans of Sarawak, East Malaysia from the 1960s to about 1990s, linking the cycle of the pattern of Iban political development to the changes in socio-economic fortune between the same period.